Penerapan Metode EOQ dalam Pengendalian Bahan Baku Guna Efisiensi Total Biaya Persediaan Bahan Baku - Sri Hastari; A Ratna Pudyaningsih; Paring Wahyudi (Jurnal Manajemen dan Kewirausahaan, 2020)
The purpose of this study is to facilitate SMEs who are members of the WASUKA cooperative in carrying out raw material inventory control to be more effective and efficient using the Economic Order Quantity (EOQ) method. This research is a descriptive analytic research type that aims to describe or provide an overview of the research object through the collected data. This study uses two data sources, namely primary data in the form of data regarding the purchase and use of raw materials and the number of order costs and storage costs. Meanwhile, other data sources are secondary data, namely data on company history, organizational structure, and other supporting data. In this study, the data collection techniques used are observation, interviews, and literature study. This research shows that the purchase of raw materials for wheat flour and peeled green beans by several SMEs in Pia Gempol village when using the EOQ method with several qualifications determined is considered quite efficient. However, the percentage is not too large. This condition may be due to the frequency of purchases made quite often so that the  order cost and storage cost is also relatively high. Besides,  the raw materials needed by several SMEs that are members of the WASUKA cooperative is considered relatively easy to obtain, considering the existence of suppliers of these raw materials close to the business location.https://doi.org/10.26905/jmdk.v8i2.4030